2013
DOI: 10.1016/j.breast.2013.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the level of breast cancer awareness among recently diagnosed patients in Ain Shams University Hospital

Abstract: Egyptian breast cancer patients knew little about their condition. Less awareness was related to age and education level. Low knowledge of risk factors, early detection and management of breast cancer should be addressed by designing patient education programs, where less educated patients are supported by health care professionals to participate in the management of breast cancer. Moreover, we found that 67% and 97% of enrolled breast cancer patients were willing as well to participate in spreading awareness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Higher breast cancer mortality rates in low and medium‐income countries (LMICs) are thought to be due to diagnosis in advanced stages and barriers to accessing medical care . Advanced stage at presentation in LMICs and in certain racial, ethnic and low socioeconomic communities in developed world are mainly because of delay in presentation to physician from onset of symptoms . In our study, the delay ranged from 3 months to more than 1 year (mean delay 8.1 ± 3.07).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Higher breast cancer mortality rates in low and medium‐income countries (LMICs) are thought to be due to diagnosis in advanced stages and barriers to accessing medical care . Advanced stage at presentation in LMICs and in certain racial, ethnic and low socioeconomic communities in developed world are mainly because of delay in presentation to physician from onset of symptoms . In our study, the delay ranged from 3 months to more than 1 year (mean delay 8.1 ± 3.07).…”
Section: Discussionmentioning
confidence: 68%
“…Khan et al revealed that there were 39.01% of patients who presented with a delay of >3 months . El‐Shinawi et al in their study done at Ain Shams University Hospital found a delay of 1 to 72 months . In comparison, the average delay in diagnosis in Eastern European countries like Hungary is 3.4 weeks (25 days), in India is 1.5 months while Ethiopia has an alarming 18‐month delay in diagnosis .…”
Section: Discussionmentioning
confidence: 98%
“…The interval between detection of the first symptoms by the patient and the first physician visit is known as patient delay (11), however, the interval between the first visit and receiving treatment is regarded as the system delay (12). Any delay in diagnosis and treatment can result in disease progression, increased mortality, and decreased survival rate (5,13,14) Several studies are available on the reasons for patient delay and a number of factors such as patients' low knowledge and education, low socioeconomic status, and family history of breast cancer have been cited in this regard (15)(16)(17)(18). However, sociocultural aspects of cancer treatment or cancer treatment seeking behaviors might be different in developing countries (13), and these two factors play an important role in timely diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In Britain, where the cultural background is sustained by rational thinking, a low percentage of the female respondents thought that breast trauma increased the risk of breast cancer. A study conducted in Egypt with women recently diagnosed with breast cancer found that 37.78% of the interviewees believed that breast trauma was a risk factor for cancer (El-Shinawi et al, 2013). Despite the strong cultural heritage and the strong influence of religion in Egypt, a low percentage of women thought that breast trauma was a risk factor for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan, a study demonstrated that 32.7% of women aged 18 to 70 years believed that wearing black clothes increases the risk of breast cancer (Sobani et al, 2012). Other factors still not widely recognized by the scientific community, such as stress (Jones et al, 2011;Lee-Lin et al, 2007;Lizama et al, 2016;Wang et al, 2010) and breast trauma, have been considered by women of different cultures as risk factors for the disease (El-Shinawi et al, 2013;Grunfeld et al, 2002;Jones et al, 2011).…”
mentioning
confidence: 99%